Transparency anticorrosion coatings prepared from alumina-covered graphene oxide/polyimide nanocomposites - G-H. Lai; T-C. Huang; I-H. Tseng; B-S. Huang; T-I. Yang; M-H. Tsai (eXPRESS Polymer Letters)
In this study, a novel alumina-covered graphene oxide/polyimide (AlGO/PI) nanocomposite was developed as an anticorrosion coating material. The hydroxyl groups on GO reacted with aluminum isopropoxide via a sol-gel process to yield AlGO nanosheets. The characterization and structure were confirmed by Fourier transform infrared spectrometry, X-ray photoelectron spectroscopy, field emission scanning electron microscopy, and field emission transmission electron microscopy. Subsequently, GO and AlGO were incorporated into a PI matrix, leading to the formation of GO/PI and AlGO/PI nanocomposites. Well-dispersed AlGO nanosheets in the PI matrix acted as effective additives to enhance the water barrier properties of GO/PI (58 g/(m2·day)) and AlGO/PI (43 g/(m2·day)) coatings. Most importantly, the resultant AlGO/PI films exhibited excellent optical transparency (>75%) and anticorrosion properties. Electrochemical measurements of corrosion potential, polarization resistance, and corrosion current as well as electrochemical impedance spectroscopy confirmed that the AlGO/PI nanocomposites exhibited better anticorrosion properties than GO/PI nanocomposites. This is likely because the insulating layer of alumina on GO can isolate the charge transfer pathway between GO and the metal substrates, leading to improved anticorrosion behavior.